2021
DOI: 10.1002/aoc.6120
|View full text |Cite
|
Sign up to set email alerts
|

Monascus pigment‐mediated green synthesis of silver nanoparticles: Catalytic, antioxidant, and antibacterial activity

Abstract: In order to explore green and efficient methods for the synthesis of nanoparticles, silver nanoparticles (AgNPs) were rapidly synthesized assisted by the Monascus pigments under simulated sunlight. Prepared AgNPs were characterized using various analytical tools such as ultraviolet‐visible (UV–Vis) spectroscopy, Zeta, X‐ray diffraction (XRD), scanning electron microscopy (SEM)–energy dispersive X‐ray (EDX), and Fourier‐transform infrared spectroscopy (FT‐IR). There is an absorption peak at 410 nm in the UV–Vis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(6 citation statements)
references
References 43 publications
1
4
0
Order By: Relevance
“…The formation of R-AgNPs was further monitored and confirmed by UV-Vis spectroscopy. Due to the surface plasmon resonance (SPR) phenomenon of R-AgNPs, R-AgNPs exhibits a visible UV absorption peak at 410 nm which is consistent with the SPR absorption peak of AgNPs in the range of 400-420 nm [33]. On the other hand, no SPR peak was shown in the silver nitrate solution at 300-800 nm, whereas the characteristic peak of rubropunctatin appeared at 467 nm in the rubropunctatin and silver nitrate mixture.…”
Section: Visible Observation and Uv-vis Spectroscopic Analysissupporting
confidence: 65%
See 1 more Smart Citation
“…The formation of R-AgNPs was further monitored and confirmed by UV-Vis spectroscopy. Due to the surface plasmon resonance (SPR) phenomenon of R-AgNPs, R-AgNPs exhibits a visible UV absorption peak at 410 nm which is consistent with the SPR absorption peak of AgNPs in the range of 400-420 nm [33]. On the other hand, no SPR peak was shown in the silver nitrate solution at 300-800 nm, whereas the characteristic peak of rubropunctatin appeared at 467 nm in the rubropunctatin and silver nitrate mixture.…”
Section: Visible Observation and Uv-vis Spectroscopic Analysissupporting
confidence: 65%
“…GL-AgNPs have good antibacterial activity against E. coli (Gramnegative) and S. aureus (Gram-positive bacteria) [37]. Rui Z et al rapidly synthesized MP-AgNPs with an average particle size of 18.10 ± 0.30 nm by monascus pigment (MP) under simulated sunlight, and demonstrated that the biosynthesized MP-AgNPs showed excellent inhibitory effects against E. coli, P. aeruginosa and S. aureus [33]. Di Filippo et al synthesized bioactive AgNPs by using snail mucus extracted from spiral snail as a bioreducing agent and bio-stabilizer.…”
Section: Discussionmentioning
confidence: 99%
“…also reported that a more efficient and environmentally friendly silver nanoparticle synthesis process was obtained with the assistance of MPs. Based on this, the utilization of pigments can be expanded to the nanomaterials application field, like commercial food packaging, pathogen mitigation and even industrial waste water management 75 . Prospectively, since antibiotics have been banned in fodder, MPs with several beneficial bioactivities may have deeper applications in livestock breeding.…”
Section: Applications Of Monascus Pigmentsmentioning
confidence: 99%
“…MPs can effectively lower blood pressure, reduce plasma cholesterol levels, prevent obesity, and improve anti-inflammatory activity. Moreover, they can be used to prevent cancer, reduce blood sugar levels, and possess anti-inflammatory and anti-tumor properties ( Yasukawa et al, 1996 , Nam et al, 2014 , Zhang et al, 2021 ).…”
Section: Introductionmentioning
confidence: 99%